2021
DOI: 10.1111/jace.17828
|View full text |Cite
|
Sign up to set email alerts
|

(W1‐x,Mx)C carbides with desired combinations of compatible density and properties – A first‐principles study

Abstract: Tungsten monocarbide (WC) is one of the most important components in hard alloys and coatings. 1 WC was originally developed based on the requirement for die materials that were able to withstand severe wear encountered in the drawing of tungsten filaments for light bulbs. However, due to its high brittleness or low fracture toughness, WC was not used widely in industry for a long period. This situation was changed with the invention of cemented carbides, where hard WC particles are embedded in a softer matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
(183 reference statements)
1
7
0
Order By: Relevance
“…Nominal fracture strengths of TaC ceramics reported in this study and by others [ 19,24,25,29,51,58–63 ] as a function of density, showing density‐dependent and flaw‐dependent strength regimes.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Nominal fracture strengths of TaC ceramics reported in this study and by others [ 19,24,25,29,51,58–63 ] as a function of density, showing density‐dependent and flaw‐dependent strength regimes.…”
Section: Resultssupporting
confidence: 71%
“…The fracture strengths of the TaC specimens from this study, 114 ± 10 MPa, are most comparable with 130–150 MPa fracture strengths reported by Shvab and Egorov [ 51 ] because of their similar densities (about 80% of theoretical density). The fracture strengths of the 90(Ta 0.8 W 0.2 )C–10WC composite specimens, 362 ± 31 MPa, are comparable with those of high‐density TaC specimens, [ 29,60–63 ] which exhibit fracture strengths from 280 to 660 MPa. The TaC composite specimens that exhibit fracture strengths greater than 425 MPa correspond to those by Hackett et al [ 60 ] and Liu et al [ 61 ] Hackett et al [ 60 ] experimented with different amounts of TaC, Ta 4 C 3− x , and Ta 2 C present in their composites and found that the increased presence of Ta 4 C 3− x leads to a higher fracture strength but can result in susceptibility to cleavage cracking.…”
Section: Resultsmentioning
confidence: 82%
“…At x = 0, the structure is unmodified, i.e., without metal substitution, while x = 1 and 2 denote the substitution of W with Cr or Mo by 25 and 50%, respectively. The crystal structures of (W 4– x , M)­C 4 can be found in ref , while the information on crystal structures of HCP and FCC cobalt comes from refs with electronic configurations of 5d 4 6s 2 , 3p 6 3d 5 4s 1 , 3d 7 4s 2 , 4p 6 4d 5 5s 1 , and 2s 2 2p 2 for W, Cr, Co, Mo, and C, respectively. The valence electrons located in the outermost energy level or shell of an atom can participate in chemical reactions and form bonds with other atoms.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Christensen et al 45 The density of WC, which is heavier than metals, can be reduced by partially substituting heavy W with metals such as Mo and Cr, while retaining the desired strength. 46 This makes them effective as reinforcements for hardfacing overlays, metalmatrix composites (MMCs) and tool materials, as they can be homogeneously dispersed in the metal matrix. It is, however, unclear if the partially substituted WC has good interfacial bonding with metals such as cobalt, one of the typical metalmatrix materials for hardfacing overlays.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation